2010
DOI: 10.1186/1471-2458-10-196
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and cost analysis for patients with oral cancer in a university hospital in China

Abstract: BackgroundAlthough several studies have reported the direct cost of oral cancer (OC), little research has invested the factors that could influence the costs of OC patient. This study analyzes the epidemiological characteristics and the direct cost of OC. More specifically, the study examines the relationship between patients' medical costs and influencing factors of epidemiology.MethodsAll patients encountered from January 2007 to December 2007 at the School of Stomatology of the Fourth Military Medical Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 20 publications
(26 reference statements)
5
34
0
2
Order By: Relevance
“…Sheng Han et al found that SCC was the major histopathogical finding in older patients (82.2% were over 40 years old). 15 In Susan Muller's et al study more than 95% of oral SCC occur in people P40 years old with a mean age of onset in the seventh decade. 16 Tobacco in all forms and alcohol consumption are the most important etiological factors predisposed to oral cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Sheng Han et al found that SCC was the major histopathogical finding in older patients (82.2% were over 40 years old). 15 In Susan Muller's et al study more than 95% of oral SCC occur in people P40 years old with a mean age of onset in the seventh decade. 16 Tobacco in all forms and alcohol consumption are the most important etiological factors predisposed to oral cancer.…”
Section: Discussionmentioning
confidence: 97%
“…It is noticeable that the diagnosis and treatment cost for patients with medicare was significantly lower than those without medicare. Comparing the cost of smokers with non-smokers, the smokers had significantly higher cost for treatment and hospitalization than those non-smokers (Han et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Although the quantity of tobacco was not defined, our results are comparable to those of Han and al in China whom reported 29.8% of smokers in their series. 7 Nevertheless that rate is lower than the one reported in Morocco (51%) and in Zimbabwe (45%). 4,8 Cigarette is a recognised causal of cancer of the oral cavity, the pharynx and the larynx like the report of Choi and al in South Korea, Raymond and al in Switzerland.…”
Section: Discussionmentioning
confidence: 66%